PERANAN PERSONIL SEKOLAH DALAM PELAKSANAAN BIMBINGAN DAN KONSELING DI SMKN 1 MANADO - Sukatma Jurnal Sukatma (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
This research was aimed at: 1) explaining positive description of the roles of school principal, counselors, vice principal, administrative personnel in SMK Negeri Manado, 2) explaining positive description on guidance and counseling program in SMK Negeri Manado, and 3) explaining the relationship among school principal, counselors, vice principal, administrative personnel in carrying out guidance and counseling program SMK Negeri Manado. The method employed in this study was survey which described factors related the roles of school principal, counselors, vice principal, administrative personnel in carrying out guidance and counseling program SMK Negeri Manado. The findings showed that there was 1) positive description about the roles school principal, counselors, vice principal, administrative personnel in SMK Negeri Manado, 2) positive description about guidance and counseling program in SMK Negeri Manado, 3) positive description about the roles school principal, counselors, vice principal, administrative personnel in carrying out guidance and counseling program in SMK Negeri Manado. These imply that positive that the roles school principal, counselors, vice principal, administrative personnel has positive influence toward guidance and counseling program in SMK Negeri Manado. Consequently, the higher the roles assumed by the school principlal, the better guidance and counseling program will be and vise versa. Based on the findings, it was suggested that 1) the school counselor keep giving information to students about guidance and counseling services that they may use. 2) School should provide facility to support guidance and counseling program, 3) students use all services provided in guidance and counseling program.Kata kunci: personil sekolah (kepala sekolah, guru BK, wali kelas, tata usaha), bimbingan dan konseling